Reclaiming the Secret of Love Feminism, Imagination and Sexual Difference - Zappone, Katherine; Zappone, Katherine; Gilligan, Anne Louise (Peter Lang, 2021)
This book presents a bold hypothesis: the social transformation at the heart of feminist theory will be concretised only when women, and men, use their imaginations to empower new ways of being in and understanding our world. Feminist theory and the history of the philosophy of the imagination are used as resources to outline how the practice of (S0(Bsexual difference(S1 (Bas an ontological vocation, and its application to religious language, can be a call to live love and mutual relations in a new way. Poetry, art, cultural and literary works are key resources too. Gilligan invites the reader to apply this theory, history and art to their own unfolding gender identities through an imagination no longer hindered by patriarchal characteristics and restrictions. She offers a special focus on the becoming of female subjectivity. She knew that if people, especially, though not only, women, image the possible for themselves and our world, through doing the hard work of becoming subject, not object of any other, such agency would necessarily change even the most intransigent social, economic and cultural problems to shift violence towards peace, lies towards truth, poverty and inequality towards the flourishing of every one. She bore witness to this in her own life, with others.s